IDENTITAS DALAM HUBUNGAN INTERNASIONAL: DILEMA KEBIJAKAN LUAR NEGERI FINLANDIA DALAM KRISIS UKRAINA 20141 - Fitri Kamelia Margareth; Mohammad Rosyid (UNIDA Gontor, 2017)
This research aims to explain why Finland did not play role as peacemaker in Ukraine Crisis. The great contribution on mediating conflicts in international relation has made Finland play role as peacemaker, a country which is well known with its peace action. But as Ukraine Crisis occurs, Finland only helps by sending foreign aid and giving advice to Russia and Ukraine to arrange a mediationwithout introducing itself as the mediator. Using constructivist approaches, this research argues that there is identity conflict between Finland’s identity as a peacemaker and as a member of The European Union which is against Russia. The strong solidarity between The European Union and Finland caused Finland tends to support The European Union’s decision to impose economic sanction against Russia, instead of mediating the conflict. This research confirms a constructivist assumption that states must consider their identities in determining foreign policy, so they will not turned dilemma when they face a situation where they need to use more than one identity to conduct foreign policy.